A decision support tool has similar high PrEP uptake and increases early PrEP persistence in adolescent girls and young women in South Africa: results from a randomized controlled trial - Connie Celum; Dominika Seidman; Danielle Travill; Christine Dehlendorf; Sanele Gumede; Kidist Zewdie; Whitney Wilson; Jennifer F. Morton; Jared M. Baeten; Deborah Donnell; Sinead Delany‐Moretlwe (Journal of the International AIDS Society, 2023)
Abstract Introduction African adolescent girls and young women (AGYW) have high rates of HIV acquisition and are a priority population for HIV pre‐exposure prophylaxis (PrEP). PrEP implementation has been limited by AGYW's low perceived HIV risk and provider demands. A decision support tool (DST) with information about PrEP could improve clients’ risk perception, knowledge about PrEP, informed decision‐making and motivation to use PrEP based on their risk, facilitating PrEP delivery in primary healthcare (PHC) clinics. Methods We designed MyPrEP, a client‐facing DST about PrEP and HIV prevention, with youth‐friendly information and images. The impact of the MyPrEP tool was assessed among HIV‐negative women aged 18–25 years presenting to a PHC clinic in Johannesburg, South Africa from March 2019 to 2020. AGYW were randomized by day to the DST or a general health website as the control condition. A clinician blinded to DST versus control allocation provided standard of care counselling about PrEP, offered PrEP, administered a questionnaire and conducted sexually transmitted infection testing. The primary outcome was PrEP initiation and the secondary outcome was PrEP persistence at 1 month, determined by pharmacy dispensation records. Results Of 386 AGYW screened, 353 were randomized (DST n = 172, control n = 181) with a median age of 21 years (interquartile range [IQR] 20, 23) and 56% (199/353) attending the clinic for HIV testing, 46% (164/353) using contraception, 15% (53/353) using condoms consistently and 37% (108/353) with a curable sexually transmitted infection. PrEP was initiated by 97% in the DST group and 94% in the control group (OR 1.79; 95% confidence interval, CI = 0.79–1.53), of whom two‐thirds planned to continue PrEP until they decided if they liked PrEP. At 1 month, PrEP persistence was 19% in the DST and 10% in the control group (OR 1.97, 95% CI 1.08–3.69). Ninety‐nine percent randomized to the DST reported satisfaction with MyPrEP. Conclusions Among AGYW attending a South African PHC clinic, PrEP uptake was >90% with two‐fold higher PrEP persistence at 1 month in those randomized to use the MyPrEP DST. Given the need for strategies to support PrEP implementation and improve low PrEP persistence among African AGYW, a PrEP DST warrants further evaluation.